EFFICACY OF EXTRACORPOREAL SHOCK WAVE THERAPY IN THE TREATMENT OF CHRONIC OSTEOARTICULAR PAIN: A SYSTEMATIC REVIEW - Oliveira, Carlos Henrique de Jesus; Freitas, André Pereira Silva; de Araujo, Danielle Fernandes; Gomes, Láysa Rodrigues de Lima; Tannus, Lorena de Oliveira (Seven Editora, 2025)
Introduction: Chronic osteoarticular pain is a debilitating condition that compromises quality of life and requires effective and safe therapeutic approaches. Objective: To evaluate the efficacy of Extracorporeal Shock Wave Therapy (ESWT) in the treatment of chronic osteoarticular pain. Methodology: Systematic review based on the PRISMA protocol, registered in PROSPERO. The search was carried out in March 2025, in the PubMed and Cochrane databases, using MESH descriptors related to ESWT and chronic pain. Randomized clinical trials published between 2020 and 2024, with adults ≥18 years old, in Portuguese, English or Spanish were included. Study selection, data extraction and assessment of risk of bias (RoB 2 tool) were conducted by independent reviewers. Results: Seven studies were selected, conducted in different countries, all in English. All studies demonstrated significant pain reduction (VAS) and functional improvement. Protocols with higher frequency and lower energy intensity showed superior short-term results. Only one study reported mild and self-limiting adverse effects. Most studies had a moderate risk of bias. Discussion: ESWT has been shown to be effective in different musculoskeletal conditions, with emphasis on its safety and analgesic potential. The heterogeneity in the protocols reinforces the need for standardization. Conclusion: ESWT is a promising, safe and effective therapy in the management of chronic osteoarticular pain, and is recommended as an alternative to conventional treatments. DOI: https://doi.org/10.56238/sevened2025.021-043